Principles of tidal sedimentology - Dalrymple, Robert W.; Davis Jr., Richard A. (Springer Netherlands, 2012)
This book presents a comprehensive, contemporary review of tidal environments and deposits.  Individual chapters, each written by world-class experts, cover the full spectrum of coastal, shallow-marine and even deep-marine settings where tidal action influences or controls sediment movement and deposition. Both siliciclastic and carbonate deposits are covered. Various chapters examine the dynamics of sediment transport by tides, and the morphodynamics of tidal systems. Several chapters explore the occurrence of tidal deposits in the stratigraphic context of entire sedimentary basins.  This book is essential reading for both coastal geologists and managers, and geologists interested in extracting hydrocarbons from complex tidal successions.